Correlation of the vancomycin 24-h area under the concentration-time curve (AUC24) and trough serum concentration in children with severe infection: A clinical pharmacokinetic study - Satja Issaranggoon na Ayuthaya (2020)
© 2020 The Author(s) Background: Vancomycin is a common drug used in children with severe infection. In adults, at least 15 mg/L of the optimal vancomycin trough concentration (Ctrough) is needed to generate the target 24-h area under the concentration-time curve (AUC24) to the minimum inhibitory concentration (MIC) of 400 for a pathogen with the MIC ≤1 mg/L. Objectives: To determine vancomycin PK in children with severe infection and to explore the correlation between vancomycin Ctrough and AUC24 in children, as well as to propose the appropriate vancomycin dosages using Monte Carlo simulation. Materials and methods: Children aged 2–18 years who were admitted to Chiang Mai University Hospital and received intravenous vancomycin for severe infection were included in the study. Serum samples for vancomycin PK were obtained before and serially after the administration of the first dose according to the protocol. Pharmacokinetic analyses were performed using Phoenix WinNonlin® 7.0 and NLME™7.0. Results: Fourteen children with 64% males and age range from 2 to 13 years were included in this study. Non-compartmental analysis revealed the median volume of distribution, clearance, and elimination half-life of 0.58 L/kg, 2.82 mL/kg/min and 2.33 h, respectively. Vancomycin serum concentrations were best described by a two-compartmental model with first-order elimination.The observed Ctrough at 6 h correlated well with the AUC24. The median vancomycin Ctrough at steady state that correlated with the AUC24 ≥ 400 and <800 were 11.18, 9.50, 7.91 and 6.55 mg/L in simulated children receiving vancomycin 40, 60, 80 and 100 mg/kg/day, respectively. Conclusion: Correlation between vancomycin Ctrough and AUC24 values in children has been observed. However, the values of Ctrough that correlate with the target AUC24≥400 in children are lower than the values observed and targeted in adults.